Characterization of the metabolic response of streptomyces clavuligerus to shear stress in stirred tanks and single-use 2d rocking motion bioreactors for clavulanic acid production (2019)
Streptomyces clavuligerus is a gram positive filamentous bacterium notable for producing clavulanic acid (CA), an inhibitor of-lactamase enzymes, which confers resistance to bacteria against several antibiotics. Here we present a comparative analysis of the morphological and metabolic response of S. clavuligerus linked to the CA production under low and high shear stress conditions in a 2D rocking-motion single-use bioreactor (CELL-tainer ®) and stirred tank bioreactor (STR), respectively. The CELL-tainer® guarantees high turbulence and enhanced volumetric mass transfer at low shear stress, which (in contrast to bubble columns) allows the investigation of the impact of shear stress without oxygen limitation. The results indicate that high shear forces do not compromise the viability of S. clavuligerus cells; even higher specific growth rate, biomass, and specific CA production rate wer observed in the STR. Under low shear forces in the CELL-tainer® the mycelial diameter increased considerably (average diameter 2.27 in CELL-tainer® vs. 1.44 m in STR). This suggests that CA production may be a ected by a lower surface-to-volume ratio which would lead to lower di usion and transport of nutrients, oxygen, and product. The present study shows that there is a strong correlation between macromorphology and CA production, which should be an important aspect to consider in industrial production of CA